Surface modification process of fly ash and application of surface modification process
Through dry surface modified fly ash technology, the problem of high cost and complex operation in the existing technology of fly ash modification in high quality and high environmental protection is solved, and the performance of rubber is significantly improved. and environmentally friendly, suitable for all kinds of solid rubbers.
Patent Information
- Application Number
- CN202411123378.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fly ash modification technology has problems such as high cost, complex operation, easy to cause secondary pollution and heat generation, and it is difficult to take into account both the reinforcement effect and low cost and high environmental protection.
The surface modification of fly ash is carried out by dry method, and by adding coupling agent one by one to the high-speed stirred fly ash, it reacts with water molecules on the surface of fly ash to form bonding, forming modified fly ash. Used as a replacement for rubber additives.
It realizes modified fly ash with simple operation, low cost and environmental protection, significantly improves the electrical insulation, thermal stability and physical and mechanical properties of rubber. It is suitable for various solid rubbers, reduces environmental pollution and reduces production costs.
Smart Images

Figure CN119144171A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a surface modification process of fly ash and application thereof, belonging to the technical field of rubber additives. Background Art
[0002] Fly ash is the main solid waste discharged from coal-fired power plants, and it is also a secondary resource containing valuable components. The comprehensive development of fly ash can not only improve its resource utilization rate and turn waste into treasure, but also effectively alleviate the problems of land resource occupation and environmental pollution caused by its long-term accumulation. The main additives of natural or synthetic rubber are calcium carbonate and carbon black, but calcium carbonate and carbon black have problems such as high raw material costs and serious production pollution. Fly ash has similar properties to calcium carbonate and carbon black. Using modified fly ash to fill rubber can save costs and improve the electrical insulation and thermal stability of rubber. The chemical composition of fly ash is similar to that of traditional fillers, and it has the characteristics of high activity. It is relatively easy to modify its surface. After surface treatment, it is easier to combine with the surface of polymer materials, thereby improving the performance of polymer materials and reducing their costs. Therefore, there is a great development prospect for the addition of fly ash to polymer materials.
[0003] The patent with publication number CN103709793A discloses a method for ultrasonically strengthening the surface modification of fly ash, wherein the fly ash after screening and drying is mixed with a solvent carbon tetrachloride, and a titanate coupling agent is added and mixed evenly to obtain modified fly ash, which is used to replace carbon black to fill natural rubber. However, carbon tetrachloride is volatile and the price of titanate coupling agent is high. Therefore, this method has the problems of easy secondary pollution and high cost. The patent with publication number CN 105273249A discloses a modified fly ash for reinforcing rubber products and a preparation method thereof, that is, the fly ash is modified by a two-coating modification method: a thermosetting resin solution is first coated on the surface of the fly ash, and then an interface adhesive solution is coated on the surface of the first coated fly ash to finally obtain the modified fly ash. The two coatings take a long time. This method has the defects of cumbersome process and complicated operation. The patent with publication number CN109134932A discloses a modified fly ash for reinforcing rubber products and a preparation method thereof, wherein the modified fly ash for reinforcing rubber products is obtained by mixing fly ash and modified mixed powder (stearic acid, aluminate paraffin, silane coupling agent, etc.), but due to the difference in properties between the substances, the mixing process is uneven, so the method has problems such as insufficient modification and high heat generation. In summary, the existing technology of using modified fly ash to fill rubber has problems such as high cost of rubber preparation, complex operation, easy to cause secondary pollution, high heat generation, etc., so there is a need for a composite material of modified fly ash that is energy-saving and environmentally friendly, has low material cost and good reinforcement effect to replace rubber additives. Summary of the invention
[0004] In order to solve the problem that it is difficult to strike a balance between reinforcement effect and low cost and high environmental protection in the existing technology of fly ash modification for filling rubber, the present application provides a fly ash surface modification process and application thereof, wherein the fly ash is modified by a dry method, and a coupling agent is added dropwise to the fly ash being stirred at a high speed, so that the coupling agent directly reacts with the water molecules on the surface of the fly ash to hydrolyze and form bonds. After the fly ash surface is modified, the composition can replace the rubber additive in the rubber filling application.
[0005] This application adopts the following technical solutions:
[0006] A surface modification process of fly ash comprises the following steps:
[0007] S1, adding each component in the coupling agent composition to an alcohol-water mixture in sequence, hydrolyzing to obtain a modifier;
[0008] The coupling agent composition includes a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent;
[0009] S2. Grind and modify the mixture containing fly ash and modifier, and dry it to obtain modified fly ash.
[0010] Optionally, in step S1, the hydrolysis conditions include: the hydrolysis temperature is 30-90° C., the hydrolysis time is 10-30 min, and the pH value is regulated to be maintained at 3-10 using weak acid and / or weak base during the hydrolysis process.
[0011] Optionally, in step S1, the hydrolysis temperature in the hydrolysis conditions is selected from any value of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or any range therebetween.
[0012] Optionally, in step S1, the hydrolysis time in the hydrolysis conditions is selected from any value of 10 min, 15 min, 20 min, 25 min, 30 min, or any range between them.
[0013] Optionally, in step S1, the weak acid is selected from at least one of silicic acid, acetic acid, phosphoric acid, and citric acid.
[0014] Optionally, in step S1, the weak base is selected from at least one of aluminum hydroxide, zinc hydroxide, ferrous hydroxide, and ferric hydroxide.
[0015] In step S1, weak acid / weak base is added dropwise during the hydrolysis process to control the pH of the water within the range of 3-10 to control the hydrolysis rate. The degree of hydrolysis is determined based on the turbidity and heat release of the liquid. After the hydrolysis is complete, the liquid is placed aside for use in subsequent experiments when mixing and stirring the fly ash.
[0016] Taking silane coupling agent as an example, the hydrolysis reaction of silane coupling agent refers to the breaking of the silicon-oxygen bond (Si-O) in its molecule under the action of water to form silanol (Si-OH) and hydroxide (OH-). This process is a reversible reaction, and its direction and rate can be controlled by adjusting the reaction conditions. Generally speaking, the hydrolysis rate of silane coupling agent is related to factors such as water concentration, pH value and hydrolysis time.
[0017] Optionally, in step S1, the alcohol content in the alcohol-water mixture is 5 to 95 wt %.
[0018] Optionally, in step S1, the alcohol is selected from at least one of methanol, ethanol, propanol and butanol.
[0019] Optionally, in step S1, the amount of each component in the coupling agent composition is:
[0020] 3 to 6 parts by weight of silane coupling agent;
[0021] 2 to 4 parts by weight of titanate coupling agent;
[0022] 1 to 2 parts by weight of aluminate coupling agent.
[0023] Optionally, in step S1, the weight ratio of the coupling agent composition to the alcohol-water mixture is 1:1-4.
[0024] Optionally, in step S2, the grinding modification conditions include: grinding temperature of 30 to 90° C., grinding time of 10 to 60 min, and grinding speed of 100 to 300 rpm.
[0025] The present application forms more aluminum oxide hexahedrons, aluminum oxide tetrahedrons and silicon oxide tetrahedrons by high-speed grinding of fly ash. The high-speed stirring process makes the coupling agent and fly ash evenly and tightly combined together, making it easier to disperse and less likely to agglomerate, which is helpful for the subsequent combination of modified fly ash and rubber.
[0026] Optionally, in step S2, the grinding temperature in the grinding modification conditions is selected from any value of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or any range therebetween.
[0027] Optionally, in step S2, the grinding time in the grinding modification conditions is selected from any value of 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any range value therebetween.
[0028] Optionally, in step S2, the grinding speed in the grinding modification conditions is selected from 100 to 300 rpm.
[0029] The grinding process includes stirring.
[0030] Optionally, in step S2, the drying conditions include: drying temperature of 90 to 110° C., and drying time of 8 to 18 hours.
[0031] Optionally, in step S2, the mixture contains:
[0032] 185-210 parts by weight of fly ash;
[0033] Modifier 30-50 parts by weight.
[0034] Optionally, in step S2, the fly ash is Class F fly ash and / or Class C fly ash.
[0035] Class F fly ash refers to fly ash whose SiO2, Al2O3 and Fe2O3 contents account for more than 70wt% of the total amount and whose CaO content is relatively low; Class C fly ash refers to fly ash whose SiO2, Al2O3 and Fe2O3 contents are between 50 and 70wt% and whose CaO content is relatively high.
[0036] Optionally, the fineness of the fly ash is 600-1200 mesh.
[0037] Optionally, in step S1, the silane coupling agent is selected from at least one of an aminosilane coupling agent, an epoxysilane coupling agent, a sulfide silane coupling agent, a methacryloxy silane coupling agent, and a propyltrimethoxy silane coupling agent.
[0038] Optionally, in step S1, the titanate coupling agent is selected from at least one of diisooctyl phosphate titanate coupling agent, p-aminophenoxy titanate coupling agent, butyl phosphate titanate coupling agent, ethylenediamine N-ethoxy titanate coupling agent, and isopropoxy trioleyl titanate coupling agent.
[0039] Optionally, in step S1, the aluminate coupling agent is selected from at least one of a distearoyloxy isopropoxy aluminate coupling agent, a methacryloyloxy aluminate coupling agent, and an isopropoxy distearoyloxy aluminate coupling agent.
[0040] According to another aspect of the present application, there is provided a use of modified fly ash prepared by the above surface modification process as a rubber additive in rubber preparation.
[0041] The modified fly ash of the present application can replace conventional rubber fillers such as calcium carbonate, carbon black, and white carbon black to be filled into rubber.
[0042] The beneficial effects of this application include:
[0043] The surface modification process of fly ash provided in the present application adopts a dry modification method, in which fly ash is poured into a high-speed mixer, and a modifier is added at a certain temperature and speed so that the modifier is coated on the outer surface of the fly ash. The process has the advantages of simple operation and easy industrialization, and is suitable for large-scale fly ash modification processes, and has a broader industrialization prospect. The modifier is first compounded with a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent, and the coupling agent is hydrolyzed in an ethanol aqueous solution. After the coupling agent is completely hydrolyzed, it is gradually added to the fly ash being ground, so that the coupling agent can be dispersed very evenly, the reinforcement effect is ideal and stable, and the grinding efficiency is greatly improved.
[0044] The fly ash obtained by the fly ash surface modification process of the present application is suitable for various solid rubbers, which overcomes the shortcomings of the fly ash in the prior art in terms of rubber performance and poor applicability of rubber varieties. Coal-fired power plants produce some by-products, such as fly ash. A large amount of fly ash accumulation will cause harm to the atmosphere, soil, and human body. The present application uses modified fly ash as a rubber additive, which can not only reduce pollution to the environment, but also achieve the purpose of energy saving and emission reduction. In addition, in the fly ash surface modification process, the materials used are all commercially available common green material products, which are truly non-toxic and harmless, meet people's requirements for environmental protection, and have the advantages of low cost and easy implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the SEM image of the unmodified fly ash in Example 1 of the present application.
[0046] Figure 2 This is the SEM image of the modified fly ash in Example 1 of the present application. DETAILED DESCRIPTION
[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0048] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0049] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0050] Example 1
[0051] The surface modification process steps of fly ash are as follows:
[0052] S1. Mix ethanol and distilled water in a beaker to prepare a 5wt% ethanol aqueous solution (alcohol-water mixture); add 3 parts by weight of propyl trimethoxy silane coupling agent (silane coupling agent), 2 parts by weight of butyl phosphate titanate coupling agent (titanate coupling agent), and 1 part by weight of isopropoxy distearic acid acyloxyaluminate coupling agent (aluminate coupling agent) as a coupling agent composition to 24 parts by weight of the alcohol-water mixture in sequence, stir with a glass rod, and perform a hydrolysis reaction at 60°C for 30 minutes. During the hydrolysis process, acetic acid / aluminum hydroxide is added dropwise to control the pH of the water within the range of 3 to 10 to control its hydrolysis rate. When the coupling agent hydrolysis begins, oil drop-like stratification occurs, and the solution gradually becomes clear while releasing heat. After the solution becomes clear and transparent, stir for another 30 minutes, and the hydrolysis is complete. After the hydrolysis is complete, a modifier is obtained.
[0053] S2. Place a mixture of 185 parts by weight of Class C fly ash (fineness is 1200 mesh) and 30 parts by weight of a modifier in a ball mill and grind and stir at 60°C for 30 minutes at a grinding speed of 180 rpm. After taking it out, dry it in a constant temperature drying oven at 100°C for 12 hours to obtain modified fly ash.
[0054] Example 2
[0055] The surface modification process steps of fly ash are the same as those of Example 1, except that 5 parts by weight of propyl trimethoxy silane coupling agent (silane coupling agent), 3 parts by weight of butyl phosphate titanate coupling agent (titanate coupling agent), and 2 parts by weight of isopropoxy distearate acyloxyaluminate coupling agent (aluminate coupling agent) are added as coupling agent compositions to 40 parts by weight of alcohol-water mixture. A mixture of 185 parts by weight of Class C fly ash (fineness of 1200 mesh) and 50 parts by weight of the modifier is placed in a ball mill.
[0056] Example 3
[0057] The process steps for surface modification of fly ash are the same as those in Example 1, except that the hydrolysis reaction is carried out at 30° C. for 30 min.
[0058] Example 4
[0059] The process steps for surface modification of fly ash are the same as those in Example 1, except that the hydrolysis reaction is carried out at 60° C. for 20 min.
[0060] Example 5
[0061] The surface modification process steps of fly ash are the same as those in Example 1, except that: 4 parts by weight of propyl trimethoxy silane coupling agent (silane coupling agent), 3 parts by weight of butyl phosphate titanate coupling agent (titanate coupling agent), and 1 part by weight of isopropoxy distearate acyloxy aluminate coupling agent (aluminate coupling agent) are added as coupling agent compositions to 32 parts by weight of alcohol-water mixture. A mixture of 185 parts by weight of Class C fly ash (fineness of 1200 mesh) and 40 parts by weight of the modifier is placed in a ball mill.
[0062] Example 6
[0063] The surface modification process steps of fly ash are the same as those in Example 1, except that grinding and stirring are performed at 75° C. for 30 min, and the grinding speed is 180 rpm.
[0064] Example 7
[0065] The process steps for surface modification of fly ash are the same as those in Example 1, except that grinding and stirring are performed at 60° C. for 45 min, and the grinding speed is 180 rpm.
[0066] Example 8
[0067] The process steps for surface modification of fly ash are the same as those in Example 1, except that the fly ash is Class F fly ash.
[0068] Example 9
[0069] The process steps for surface modification of fly ash are the same as those in Example 1, except that grinding and stirring are performed at 60° C. for 30 min, and the grinding speed is 120 rpm.
[0070] Example 10
[0071] The process steps for surface modification of fly ash are the same as those in Example 1, except that the coupling agent composition is sequentially added into 48 parts by weight of the alcohol-water mixture.
[0072] Test Example 1
[0073] The surface morphology of the unmodified fly ash and the modified fly ash obtained in Example 1 was tested using a TESCAN hot wire emission scanning electron microscope-VEGA3:
[0074] like Figure 1 As shown in the figure on the left, the unmodified fly ash particles coexist in the form of particles and microspheres, and there are large blocks, indicating that they are seriously agglomerated and not conducive to compatibility with rubber. Figure 2As shown, the fly ash after modification in Example 1 is mainly in the form of microspheres and has a high degree of dispersion. This is because the coupling agent on the surface of the particles is hydrophobic, which prevents the agglomeration of the fly ash particles and promotes the dispersion of the fly ash, thereby improving its compatibility with the rubber raw material.
[0075] Test Example 2
[0076] 100 kg of different rubbers were reinforced with 15 kg of the modified fly ash prepared in Examples 1 to 10 (the selection of rubbers is shown in Table 1), and the specific reinforcement method was:
[0077] The rubber was first plasticized on a two-roll rubber mill for 35 minutes, and then mixed with fly ash on a two-roll rubber mill for 10 minutes. Then, activator ZnO, accelerator dithiocarbamate and sulfur were added to the composition, and grinding was continued for 15 minutes. Then, the compounded material was formed into a sheet with a size of 150mm×150mm×6mm in a compression molding machine at 160°C and 30 tons of pressure. The results of various indicators of the reinforced natural rubber are shown in Table 1:
[0078] Table 1
[0079]
[0080] From the test results of rubber tensile strength, elongation at break, 100 constant elongation, 300 constant elongation, Shore hardness, permanent deformation and other properties of the test examples, it can be seen that in the process of dry modification, the modification effect of Class C fly ash is better, the optimal ratio of silane coupling agent, titanate coupling agent and aluminate coupling agent is 3:2:1, the diluent is ethanol solution, the optimal modification temperature is 60°C, the optimal modification time is 30min, and the optimal speed is 180rpm. The optimal weight ratio of the coupling agent composition to the alcohol-water mixture is 1:8. Filling the modified fly ash into natural rubber, nitrile rubber, and styrene-butadiene rubber significantly improves its strength and hardness, while also improving durability, increasing service life, and improving the use efficiency of rubber products. At the same time, since fly ash has fine particles and a large specific surface area, it has good filling properties. Adding it to rubber can fill the gaps in the rubber material, thereby improving the density and physical and mechanical properties of rubber products. Finally, fly ash can also improve the properties of rubber. The modified fly ash surface will form a protective layer in the rubber, which can effectively prevent cracks and wear under load, and also improve the heat resistance and chemical resistance of rubber materials.
[0081] The application of fly ash in rubber can not only effectively improve the performance of rubber products, but also solve the environmental problems existing in traditional fillers. Therefore, with the increasing requirements for environmental protection and ecological environment protection, and the deepening of the concept of energy conservation and emission reduction, the modified fly ash of the present invention replaces the rubber additive composite material, and its application prospect in rubber is very promising, and it will definitely become a new green filler.
[0082] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A surface modification process for fly ash, characterized in that: The steps include: S1, adding each component in the coupling agent composition to an alcohol-water mixture in sequence, hydrolyzing to obtain a modifier; The coupling agent composition includes a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; S2. Grind and modify the mixture containing fly ash and modifier, and dry it to obtain modified fly ash.
2. The surface modification process according to claim 1, characterized in that: In step S1, the hydrolysis conditions include: the hydrolysis temperature is 30-90°C, the hydrolysis time is 10-30 minutes, and the pH value is regulated to be maintained at 3-10 using weak acid and / or weak base during the hydrolysis process.
3. The surface modification process according to claim 1, characterized in that: In step S1, the alcohol content in the alcohol-water mixture is 5 to 95 wt %; Preferably, in step S1, the alcohol is selected from at least one of methanol, ethanol, propanol and butanol.
4. The surface modification process according to claim 1, characterized in that: In step S1, the dosage of each component in the coupling agent composition is: 3 to 6 parts by weight of silane coupling agent; 2 to 4 parts by weight of titanate coupling agent; 1 to 2 parts by weight of aluminate coupling agent.
5. The surface modification process according to claim 1, characterized in that: In step S1, the weight ratio of the coupling agent composition to the alcohol-water mixture is 1:1-4.
6. The surface modification process according to claim 1, characterized in that: In step S2, the grinding modification conditions include: grinding temperature of 30-90° C., grinding time of 10-60 min, and grinding speed of 100-300 rpm.
7. The surface modification process according to claim 1, characterized in that: In step S2, the mixture contains: 185-210 parts by weight of fly ash; Modifier 30-50 parts by weight.
8. The surface modification process according to claim 1, characterized in that: In step S2, the fly ash is Class F fly ash and / or Class C fly ash; Preferably, the fineness of the fly ash is 600-1200 mesh.
9. The surface modification process according to claim 1, characterized in that: In step S1, the silane coupling agent is selected from at least one of an aminosilane coupling agent, an epoxysilane coupling agent, a sulfide silane coupling agent, a methacryloxy silane coupling agent, and a propyltrimethoxy silane coupling agent; Preferably, in step S1, the titanate coupling agent is selected from at least one of diisooctylphosphoacyloxy titanate coupling agent, p-aminophenoxy titanate coupling agent, butylphosphoacyl titanate coupling agent, ethylenediamine N-ethoxy titanate coupling agent, and isopropoxy trioleyl titanate coupling agent; Preferably, in step S1, the aluminate coupling agent is selected from at least one of a distearoyloxy isopropoxy aluminate coupling agent, a methacryloyloxy aluminate coupling agent, and an isopropoxy distearoyloxy aluminate coupling agent.
10. Use of the modified fly ash prepared by the surface modification process according to any one of claims 1 to 9 as a rubber additive in rubber preparation.
Citation Information
Patent Citations
Fly ash ultrasound-enhanced surface modification and application to replace carbon black filled rubber
CN103709793A
Modified fly ash for reinforcing rubber products and preparation method thereof
CN105273249A
Modified flyash for reinforcing rubber products and preparation method of modified flyash
CN109134932A
Pulverized coal ash rubber reinforcing agent
CN102010535A
Method and application for carrying out fly ash floating bead surface modification by using compound coupling agent
CN102850825A
